Optimasi Pemeliharaan Mesin Rajut di UMKM KN Collection Dengan Menggunakan Metode Total Productive Maintenance (TPM) - Ramadhan, Sahrul; Taptajani, Dedi Sa'duddin (Institut Teknologi Garut, 2025)
KN Collection UMKM is a small to medium-sized enterprise engaged in the production of knitted caps. In its operations, this production unit still faces various challenges that impact the achievement of optimal production targets. Some common issues encountered in the field include the high downtime of knitting machines, which causes sudden production halts and disrupts the overall workflow. Additionally, production targets are often not met, both in terms of quantity and completion time, due to the unstable performance of the machines. In this research, I propose improvements using the Total Productive Maintenance (TPM) method to reduce machine performance degradation and downtime on the knitting machines. TPM is applied to maintain and optimize equipment efficiency, eliminate failures, and provide maintenance recommendations through daily operations involving all personnel.The results of measuring the knitting machines using the Overall Equipment Effectiveness (OEE) method at KN Collection MSME showed an increase in the OEE value from 69% to 89%. The highest OEE value occurred in March at 89%, while the lowest was in February at 69%, which is close to the ideal OEE standard threshold of 85%. The most significant loss contributing to the low OEE value was speed loss, which accounted for 117%. To optimize maintenance at KN Collection MSME, it is recommended to provide training on procedures to predict potential machine failures, so that operators can immediately report issues to the maintenance department for follow-up action.